Diagnosis, management, and long-term outcomes of rectovaginal endometriosis - Moawad NS; Caplin A (Dove Medical Press, 2013)
Nash S Moawad,1 Andrea Caplin21Minimally Invasive Gynecologic Surgery, Department of Obstetrics and Gynecology, University of Florida, 2University of Florida College of Medicine, Gainesville, FL, USAAbstract: Rectovaginal endometriosis is the most severe form of endometriosis. Clinically, it presents with a number of symptoms including chronic pelvic pain, dysmenorrhea, deep dyspareunia, dyschezia, and rectal bleeding. The gold standard for diagnosis is laparoscopy with histological confirmation; however, there are a number of options for presurgical diagnosis, including clinical examination, transvaginal/transrectal ultrasound, magnetic resonance imagining, colonoscopy, and computed tomography colonography. Treatment can be medical or surgical. Medical therapies include birth control pills, oral progestins, gonadotropin-releasing hormone agonists, danazol, and injectable progestins. Analgesics are often used as well. Surgery improves up to 70% of symptoms. Surgery is either ablative or excisional, and is conducted via transvaginal, laparoscopic, laparotomy, or combined approaches. Common surgical techniques involve shaving of the superficial rectal lesion, laparoscopic anterior discoid resection, and low anterior bowel resection and reanastomosis. Outcomes are generally favorable, but postoperative complications may include intra-abdominal bleeding, anastomotic leaks, rectovaginal fistulas, strictures, chronic constipation, and the need for reoperation. Recurrence of rectal endometriosis is a possibility as well. Other outcomes are improved pain-related symptoms and fertility. Long-term outcomes vary according to the management strategy used. This review will provide the most recent approaches and techniques for the diagnosis and treatment of rectovaginal endometriosis.Keywords: pelvic pain, dyspareunia, bowel resection, endometriosis, rectovaginal